Towards a dietary-exposome assessment of chemicals in food: An update on the chronic health risks for the European consumer - Eskola, Mari; Elliott, Christopher T; Hajšlová, Jana; Steiner, David; Krska, Rudolf (Critical reviews in food science and nutrition, 2020)
An informed opinion to a hugely important question, whether the food on the Europeans' plate is safe to eat, is provided. Today, the Europeans face food-borne health risks from non-communicable diseases induced by excess body weight, outbreaks caused by pathogens, antimicrobial resistance and exposures to chemical contaminants. In this review, these risks are first put in an order of importance. Then, not only potentially injurious dietary chemicals are discussed but also beneficial factors of the food. This review can be regarded as an attempt towards a dietary-exposome evaluation of the chemicals, the average European adult consumers could chronically expose to during their life-times. Risk ranking reveals that currently the European adults are chronically exposed to a mixture of potentially genotoxic-carcinogenic contaminants, particularly food process contaminants, at the potential risk levels. Furthermore, several of the contaminants whose dietary exposures pose risks appear to be carcinogens operating with a genotoxic mode of action targeting the liver. This suggests that combined health risks from the exposure to a mixture of the chemical contaminants poses a greater potential risk than the risks assessed for single compounds. Over 100 European-level risk assessments are examined. Finally, the importance of a diversified and balanced diet is emphasized.
Keywords: dietární expozice; contaminants; Europeans; Humans; Exposure; risk assessment; dospělí; Exposome; lidé; Europe; expozom; Adult; kontaminace potravin; Food Contamination; Carcinogens; Dietary Exposure; residues; karcinogeny; Risk Assessment; Food; potraviny; hodnocení rizik; Evropa